Hip, knee, and ankle kinematics during activities of daily living: a cross-sectional study - Hyodo, Kashitaro (Braz J Phys Ther, 2017)
BACKGROUND: Joint angle data from healthy subjects are necessary as baseline information. OBJECTIVE: To analyze the problems of patients who struggle with activities of daily living (ADL) due to restricted range of motion and to provide ADL guidance based on objective data. METHOD: An electromagnetic three-dimensional tracking system (FASTRAK) was used to quantify the hip, knee, and ankle angles of the dominant leg of 26 healthy adults as they performed 22 ADLs related to dressing, using the toilet, bathing, picking up objects, and crouching. For each ADL, the maximum angle was averaged across the 26 subjects. Mean angles of adduction/abduction and internal/external rotation during maximum hip flexion were also measured. RESULTS: The largest mean maximum angle was 101° for hip flexion (trunk rotation during crouching), 17° for hip adduction (putting on shoes), and 149° for knee flexion (trunk rotation during crouching). Analysis of adduction/abduction and internal/external rotation angles during maximum hip flexion showed the largest angle of adduction when putting on shoes, and the largest angle of internal rotation with trunk rotation during crouching. CONCLUSIONS: ADLs such as crouching and putting on pants showed larger joint angles than walking, climbing stairs, and standing up. Results obtained from this study can provide important objective data for ADL guidance for total hip arthroplasty and femoroacetabular impingement patients.